Implementasi Pendidikan Karakter Berbasis Keagamaan Dalam Memperkuat Ketahanan Keluarga Pada Masa Pandemi Di Kecamatan Karangasem - I Wayan Sudiarta; I Kadek Edi Palguna (Jayapangus Press, 2021)
The Covid 19 outbreak in Indonesia has spread to various regions, becoming the epicenter of the spread of the virus. This makes the joints of family resilience to be shaky due to various impacts. The purpose of this study is to determine the need for religious-based character education to be implemented, how to implement Religious-Based character education in strengthening family resilience during the pandemic in Karangasem District, and the implications of Religious-Based Character Education on Family Resilience during the Pandemic Period in Karangasem District. The method used is descriptive qualitative with the type of data used in this study is qualitative data. The source of data used is primary data, namely data obtained from informants and secondary data in the form of literature as supporting primary data. The process of data analysis in an interactive form. The results of the research obtained are considering the many problems faced by the community in Karangasem District, especially problems in the aspects of tourism and trade, it is necessary to implement character education during the pandemic for family resilience, the form of Implementation of Religious-Based Character Education, which is reflected in the teachings of Tri Kaya Parisuda, namely thinking (manacika), taste/intention (wacika) and exercise (Kayika), and the implications of religious-based character education on family resilience during a pandemic in Karangasem district, namely being able to strengthen psychological resilience with awareness to be able to control oneself and accept all conditions sincerely. and keep trying and keep trying to find solutions and solutions. From some of the informants' explanations, the implementation of religious-based character education is very important to strengthen family resilience during the pandemic.